On-station performance of new Hevea clones in the pipeline in Phase 1 Participatory trial in India - Meenakumari, T (Rubber Science, 35(1): 62-71., 2022)
Thirteen new Hevea clones along with three check clones viz. RRII 105, RRII 414 and RRII 430 were evaluated over a period of 12 years for growth, early yield, disease incidence and other desirable secondary traits in a large scale station trial as part of Participatory Clone Evaluation (PCE) programme (Phase 1) in Central Kerala, India. Among these, five clones viz., P 44, P 26, P 63, P 64 and P 70 were found to hold promise in terms of growth, dry rubber yield in the early phase and desirable component traits including disease tolerance compared to control clones. Clones developed through recombination and polycross breeding approaches performed equally well. The high leaf retention in P 63 and P 70 even under the combined attack of abnormal leaf fall and circular leaf spot disease was noteworthy. The performance of new cohort of clones in this central researcher trial will be compared with that of the satellite on farm trials to identify better region-wise adaptive clones for the future.
Keywords: Bark anatomy; Growth; New Hevea clones; Participatory clone evaluation; Yield